American-Australian relations - Levi, Werner, 1912-2005 (University of Minnesota Press ; G. Cumberlege, Oxford University Press, 1947)
This new study fills a wide gap in the story of American-Australian relations and is a timely addition to the literature in this field. There has been no comprehensive treatment of the topic before, and it will be of interest to those seeking information.